The effect of vitamin D therapy on inflammatory markers in patients with type 2 diabetes mellitus and diabetic peripheral polyneuropathy - Anna P. Stepanova; Tatiana L. Karonova (Сахарный диабет)
BACKGROUND: The pathogenesis of diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes mellitus (T2DM) is multifactorial, and includes increased inflammation. In recent years, the effect of vitamin D therapy on improving the profile of inflammatory parameters has been actively studied. AIMS: The aim of this study was to assess inflammation markers before and after various doses of cholecalciferol therapy in T2DM with DPN. MATERIALS AND METHODS: Single-center open randomized study included T2DM patients with PDN. Sixty-seven patients were randomized into 2 groups. For 24 weeks Group I have been taking a dosage of cholecalciferol 5,000 IU/week, and Group II a dosage of 40,000 IU/week. At the baseline and in the end of the research there have been studied body mass index (BMI), glycated hemoglobin (HbA1c), 25-hydroxyvitamin D (25(OH)D), PTH, interleukin-1β, -6, -10 (IL), C-reactive protein (CRP), tumor necrosis factor -α (TNFα). RESULTS: Sixty-two patients completed the study. Group I (n=31, F16), Group II (n=31, F15) were initially compared by age, sex, BMI and НbA1clevel. Vitamin D deficiency/insufficiency was detected in 78% of patients with T2DM. After 24 weeks of therapy with cholecalciferol in Group II there was a significant decrease in BMI, HbA1c, IL-6 levels and an increase in IL-10 levels while no changes were found in Group I. There has been established a correlation between the final level of 25(OH)D and IL-6 (r=-0.378, p=0.036), IL-10 (r=0.483, p=0.006), BMI (r=-0.388, p=0.031) and НbA1c(r=-0.388, p=0.031). CONCLUSION: The intake of cholecalciferol at a dosage of 40,000 IU/week for 24 weeks is associated with a decrease in BMI, improvement of glycemic control and pro-inflammatory markers profile in patients with T2DM with DPN. Study results showed that the normalization of serum 25(OH)D level can be one of the modifying factors for the development and progression of DPN in patients with T2DM.